All the Routes for Laparoscopic Liver Segment VIII Resection: A Comprehensive Review of Surgical Techniques - Anselmo, Alessandro; Sensi, Bruno; Bacchiocchi, Giulia; Siragusa, Leandro; Tisone, Giuseppe (Frontiers in Oncology, 2022)
Liver surgery is highly demanding for anatomical, physiological and technical reasons and minimally invasive approaches have been implemented at a slower rate. Today, laparoscopic liver resection is a standard of care in many occasions, yet specific operations remain particularly challenging and generally performed in open surgery. In particular SVIII resection may be considered one of the most difficult due to anatomical characteristics including its sub-diaphragmatic position, the deep lying glissonean-pedicle and the close contact with inferior vena cava, right and middle hepatic veins. Many techniques have risen to overcome technical difficulties and today laparoscopic SVIII resection has been demonstrated to be feasible. This review focuses provides a complete picture of current approaches, focusing on all techniques reported so far with critical appraisal of each, discussing and explaining benefits and pitfalls.